2022
DOI: 10.1186/s40798-022-00538-4
|View full text |Cite
|
Sign up to set email alerts
|

Is Postural Control Affected in People with Patellofemoral Pain and Should it be Part of Rehabilitation? A Systematic Review with Meta-analysis

Abstract: Background Growing evidence supports that exercise therapy is effective for patellofemoral pain (PFP) rehabilitation. Nevertheless, the improvements have been reported not to be sustained in the long term, suggesting that the current protocols may not comprehend all required functional factors to provide a consistent recovery. A potential neglected factor in treatment protocols for PFP is postural control. However, it is unclear whether this population presents balance impairments or the influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 133 publications
0
1
0
Order By: Relevance
“…The ratings for those categories were ‘No serious’, ‘Serious’, and ‘Very serious’. The level of evidence certainty was downgraded if the meta-analysis (i) included 25% of studies with poor quality assessed by QAT (1 level of Risk of bias) or all studies with poor quality (2 level of Risk of bias), (ii) showed higher than 50% of I 2 (1 level of Inconsistency)—I 2 values have been used previously to evaluate inconsistency in CoP outcomes 34 , 35 —(iii) did not include direct evidence related to the main question (1 level of Indirectness), (vi) included less than the optimal sample size (n = 244) calculated based on 5% of margin of error, 95% confidence intervals, and total sample size (n = 663; 1 level of Imprecision), and (v) showed publication bias resulting from Egger’s regression and trim and fill test (1 level of Publication bias). Combining all the ratings, the certainty of the evidence in meta-analyses were interpreted based on four levels: ‘High’, ‘Moderate’, ‘Low’, and ‘Very low certainty’.…”
Section: Methodsmentioning
confidence: 99%
“…The ratings for those categories were ‘No serious’, ‘Serious’, and ‘Very serious’. The level of evidence certainty was downgraded if the meta-analysis (i) included 25% of studies with poor quality assessed by QAT (1 level of Risk of bias) or all studies with poor quality (2 level of Risk of bias), (ii) showed higher than 50% of I 2 (1 level of Inconsistency)—I 2 values have been used previously to evaluate inconsistency in CoP outcomes 34 , 35 —(iii) did not include direct evidence related to the main question (1 level of Indirectness), (vi) included less than the optimal sample size (n = 244) calculated based on 5% of margin of error, 95% confidence intervals, and total sample size (n = 663; 1 level of Imprecision), and (v) showed publication bias resulting from Egger’s regression and trim and fill test (1 level of Publication bias). Combining all the ratings, the certainty of the evidence in meta-analyses were interpreted based on four levels: ‘High’, ‘Moderate’, ‘Low’, and ‘Very low certainty’.…”
Section: Methodsmentioning
confidence: 99%
“…This syndrome can limit functional performance and intensively affect the quality of life (6). Also, some studies showed balance impairments in PFPS (7)(8)(9)(10)(11)(12)(13), but the recent systematic review study indicated that there is a controversy between studies about balance deficits in these patients (14). Dynamic balance is defined as the ability to do a task while maintaining a stable position (15) and is a basic need for independent activities of daily living (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%